2011
DOI: 10.1038/bjc.2011.215
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Epstein-Barr virus-positive gastric cancer: an international pooled analysis

Abstract: Background:Meta-analyses of the published literature indicate that about 9% of gastric cancers contain Epstein-Barr virus (EBV), with consistent and significant differences by sex and anatomic subsite. This study aimed to identify additional determinants of EBV positivity and their joint effects.Methods:From 15 international populations with consistent laboratory testing for EBV, we pooled individual-level data for 5081 gastric cancer cases including information on age, sex, subsite, histologic type, diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
4
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 31 publications
10
100
4
2
Order By: Relevance
“…EBV-associated gastric cancer type differs from other gastric cancers, exhibiting male predominance, non-antral anatomic subsites and better survival (6,7,17,18). Our results showed that EBVaGC was significantly more frequent in the higher metabolic tumor group than the lower metabolic group.…”
Section: Discussionsupporting
confidence: 54%
“…EBV-associated gastric cancer type differs from other gastric cancers, exhibiting male predominance, non-antral anatomic subsites and better survival (6,7,17,18). Our results showed that EBVaGC was significantly more frequent in the higher metabolic tumor group than the lower metabolic group.…”
Section: Discussionsupporting
confidence: 54%
“…Gastric carcinoma is not only the most common EBVassociated malignancy in South Korea but the most common cancer overall in South Korea (8,9,41). EBV-positive gastric carcinomas show distinct clinicopathological characteristics, including lymphoid stroma (7,10), a higher prevalence in male patients and poorly differentiated WHO-type and diffuse Laurentype tumors (7,11), less frequent metastasis to lymph nodes (10), predominant localization to the proximal stomach (7,(10)(11)(12), unique expression of many cancer-related genes (7,9,12), and global CpG island methylation of cancer-related gene promoters (6).…”
mentioning
confidence: 99%
“…Se sabe que el CaGVEB se presenta en 2 % a 20 % de la población mundial. Anualmente se diagnostican de 200 000 a 876 000 casos nuevos de CaGVEB, que causan 69 081 a 90 000 muertes cada año (77,(80)(81)(82)(83). En Colombia, la tasa más alta de mortalidad por CaGVEB se reporta en regiones montañosas y la más baja, en regiones planas; es más frecuente en hombres jóvenes y el subtipo histológico predominante es el adenocarcinoma de tipo difuso (84).…”
Section: Veb Y Cáncer Gástrico (Cg)unclassified